التجديد الفقهي حول العمل بمبدأ الاحتياط لأجل سدّ الذرائع: دراسة فقهية تحليلية مقارنة: Jurisprudence renewal about working with the principle of precaution in order to leave the suspicious things: A comparative and analytical jurisprudence study - Israr Khan; Hafiz Abdul Rehman; Mufti Muhammad Shah Faisal (jihat-ul-islam, 2022)
In the current era, work has increased on the principle of precaution to leave suspicious things after increasing the doubts in contemporary matters. So the question is that, is it necessary to leave all suspicious matters acting upon precaution principle or not? Therefore, it is necessary to search for jurisprudential judgment in these suspicions matters. But when we read the opinions of the jurists in this regards, we find that some of them allowed working with it and some of them prohibited working with it. As for this paper, it makes comparison between these two opinions discussing their evidences. Further, it also clarifies this principle position in these suspicious matters. So by studying this paper scholars will be able to apply it on contemporary suspicions matters without exaggeration or negligence.